Mapping the Depth of Groundwater Level and Soil Permeability Based on Geographic Information Systems (GIS) for The Feasibility of Absorption Well Locations in The Application of Ecodrain in Tuah Madani District - Joleha; 'Audah, Safridatul; Handayani, Yohanna Lilis; Suprayogi, Imam (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The problem of flooding in Tuah Madani District, Pekanbaru City, needs attention. Drainage and flood control systems need to be made to accommodate excess water and hold water somewhere. Groundwater management is directed at creating a balance between groundwater utilization and soil conservation efforts through the application of ecodrain which affects the conditions and characteristics of the area which provides an overview of land hydrology in parcels by comparing the height of the land with the receiving water bodies. as a drainage outlet. This research aims to create a map of groundwater depth and soil permeability based on Geographic Information Systems (GIS) for the feasibility of infiltration well locations in Tuah Madani District in implementing ecodrain. The research method was carried out by collecting data on the coordinates of infiltration wells at 30 points in five areas of Tuah Madani District. then measure the depth of the groundwater table and test the permeability in the field. Data is processed using ArcGIS. The results of mapping the depth of the groundwater table in the area are classified as shallow (1.28m–3.58m). Only 4 locations (Tuah Karya and West Sidomulyo) out of 30 sample locations did not meet the standards. Meanwhile, the permability value obtained was 2.61–11.07 cm/hour. Technically, the procedure for planning infiltration wells (SNI03-2453-2002) fulfills two conditions, namely a minimum groundwater depth of 1.50 m and soil permeability ≥ 2.0 cm/hour. Based on the contour lines of Tuah Madani District, it displays a pattern of groundwater flow from high flow to low flow at each point of the wellbore, the highest points on the map are colored blue (Air Putih and Sidomulyo Barat), while the lowest points on the map are Air Putih and Sidomulyo Barat. red (Tuah Madani, Luah Karya and Sialangmunggu).